2010
DOI: 10.1002/adfm.201090104
|View full text |Cite
|
Sign up to set email alerts
|

Edible Electronics: Biocompatible and Biodegradable Materials for Organic Field‐Effect Transistors (Adv. Funct. Mater. 23/2010)

Abstract: Biocompatible‐ingestible electronic circuits and capsules for medical diagnosis and monitoring are currently based on traditional silicon technology. Organic electronics has huge potential for developing biodegradable, biocompatible, bioresorbable, or even metabolizable products. An ideal pathway for such electronic devices involves fabrication with materials from nature, or materials found in common commodity products. Transistors with an operational voltage as low as 4–5 V, a source drain current of up to 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…For instance, an in vivo investigation of fully hydrated melanin thin films with conductivities of 7 × 10 –5 S/cm revealed that the melanin implants are almost fully eroded and resorbed after 8 weeks . Other eco-friendly and biodegradable natural conjugated materials include the molecule accountable for the orange color of carrots, β-carotene and byproducts of a natural laxative, anthraquinone. , Although these natural or nature-inspired conjugated molecules possess exciting potential, strict processing constraints are required to attain the most advantageous morphology and orientation for sufficient device performance . Thus, to better understand and predict the future of these materials, a greater assessment of charge transfer and electrochemical features is required .…”
Section: Structural and Functional Materials For Biodegradable Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, an in vivo investigation of fully hydrated melanin thin films with conductivities of 7 × 10 –5 S/cm revealed that the melanin implants are almost fully eroded and resorbed after 8 weeks . Other eco-friendly and biodegradable natural conjugated materials include the molecule accountable for the orange color of carrots, β-carotene and byproducts of a natural laxative, anthraquinone. , Although these natural or nature-inspired conjugated molecules possess exciting potential, strict processing constraints are required to attain the most advantageous morphology and orientation for sufficient device performance . Thus, to better understand and predict the future of these materials, a greater assessment of charge transfer and electrochemical features is required .…”
Section: Structural and Functional Materials For Biodegradable Sensorsmentioning
confidence: 99%
“…A variety of additional natural compounds, including bio-organics, such as sodium alginate and even foodstuffs, like charcoal, rice paper, potato starch, gelatin seaweed, and cheese, have also been used as natural substrates for biodegradable devices. 22,116 2.1.2. Synthetic Polymer Substrate.…”
Section: Structural and Functional Materials For Biodegradable Sensorsmentioning
confidence: 99%
“…Consequently, the unique electronic signatures of highly evolved biological materials can be harnessed into device architectures. Materials that can be isolated from the native environment and repurposed into thin film technologies may serve as useful device technologies ( Figure ) 3. This section presents an emerging theme of recapitulating biologically‐derived semiconductors, insulators, and metals as components in electronic devices.…”
Section: Biologically‐derived Materials As Active Components In Elmentioning
confidence: 99%
“…Hydrophilic biopolymers are perfectly suitable for gate dielectrics while a wide range of polymers, both natural and synthetic, are appropriate for use as flexible device substrates with additional capabilities such as compostability and bioabsorbability. Reproduced with permission 3…”
Section: Biologically‐derived Materials As Active Components In Elmentioning
confidence: 99%
“…In this perspective, hydrogels, [9,10] soft polymers, [11] and plant-derived natural compounds [12] have showed stable performance as conductors, insulators and semiconductors. [13] Among these, the use of paper or cellulose-based materials has been widely explored as substrate material [14] for flexible electronics. Although reliable recycling processes allow infinite and sustainable reuse of cellulose, the materials employed in the device stack (i.e., toxicants, pollutants, rare-Earth elements) are still limiting factors, to achieve a green transition.…”
Section: Introductionmentioning
confidence: 99%